2021
DOI: 10.1186/s12913-021-07222-5
|View full text |Cite
|
Sign up to set email alerts
|

Navigating medical assistance in dying from Bill C-14 to Bill C-7: a qualitative study

Abstract: Background Even as healthcare providers and systems were settling into the processes required for Medical Assistance in Dying (MAID) under Bill C-14, new legislation was introduced (Bill C-7) that extended assisted death to persons whose natural death is not reasonably foreseeable. The purpose of this paper is to describe the experiences of nurses and nurse practitioners with the implementation and ongoing development of this transition. Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…An important decision for each province and territory has been how to set up MAID services in a way that balances safety with accessibility ( Wiebe et al, 2021 ). One of the initial challenges was accessibility to MAID ( Oczkowski et al, 2021a , 2021b ), in part, because of the difficulties in finding sufficient MAID assessors and providers across the vast geographic distances of Canada ( Pesut, Thorne, Wright, et al, 2021 ; Wiebe et al, 2021 ). Many primary care providers chose not to act as MAID assessors and/or providers for a variety of reasons in addition to conscientious objection.…”
Section: Discussionmentioning
confidence: 99%
“…An important decision for each province and territory has been how to set up MAID services in a way that balances safety with accessibility ( Wiebe et al, 2021 ). One of the initial challenges was accessibility to MAID ( Oczkowski et al, 2021a , 2021b ), in part, because of the difficulties in finding sufficient MAID assessors and providers across the vast geographic distances of Canada ( Pesut, Thorne, Wright, et al, 2021 ; Wiebe et al, 2021 ). Many primary care providers chose not to act as MAID assessors and/or providers for a variety of reasons in addition to conscientious objection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the short interval from first assessment to completion of MAID in our study is compatible with our finding that most patients had poor performance status at the time of MAID request. Of note, following the time period investigated in our study, a change in the Canadian MAID legislation occurred on 17 March 2021 that removed the 10 day waiting period for MAID in patients with a reasonably foreseeable natural death [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some may ask themselves whether the patient is suicidal or not, has a comorbid psychiatric disorder, or has lost capacity to consent. 6 , 15–18 Preliminary data revealed that assessors are interested in further training on psychiatric aspects. 19 Centering MAiD on the patient's needs remains a complex task.…”
Section: Patients-partners' Contribution To Educational Challengesmentioning
confidence: 99%
“…In Canada, the province of Quebec gave access to Medical Assistance in Dying (MAiD) 5 in December 2015, as it became accessible across the rest of Canada in June 2016. 6 , 7 MAiD was first an end-of-life option, but its accessibility has expanded, including to those whose death is not foreseeable. 8 It is still an evolving practice.…”
Section: Introductionmentioning
confidence: 99%